Collecting practices and opisthographic collections in Qumran and Herculaneum - Aksu, Ayhan (2025)
In Collecting Practices and Opisthographic Collections in Qumran and Herculaneum , Ayhan Aksu offers a new perspective on practices of collection in both the Dead Sea Scrolls and the Herculaneum papyri. This study focuses on the intriguing question how ancient scribes and scholars used manuscripts to bring different texts in conversation with each other. Central to Aksu’s approach are opisthographic manuscripts – scrolls that contain text on both the front and back side. Comparative research of the rich papyrus collection from Herculaneum reveals that scribes across various regions of the Mediterranean developed dynamic approaches to engage with their texts.